Role of arterial spin labeling magnetic resonance perfusion in acute ischemic stroke - Ahmed Adel ElBeheiry; Mohamed Ahmed Hanora; Ahmed Farid Youssef; Abdel Aziz Mohamed Al Neikedy; AbdelRahman Elhabashy; Hamada Mohamed Khater (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Arterial spin labeling (ASL) is a recently used magnetic resonance imaging (MRI) perfusion technique in acute cerebrovascular stroke conditions; it can detect the hypo perfused areas on basis of qualitative and quantitative measurements and also identify the area at risk known as penumbra by detecting the diffusion/perfusion mismatch. The purpose of this study was to assess the role of ASL perfusion technique in management of acute ischemic stroke and its ability to predict the clinical outcome of acute stroke patients. The study was prospectively carried out on 33 patients clinically presented with acute stroke from the first of August 2020 till the first of August 2021. All cases were clinically assessed by stroke consultant followed by brain imaging including conventional MRI and ASL perfusion technique, based upon which management was established. These imaging data were correlated with the clinical outcome after 3 months using Modified Rankin Scale. Results Sixteen cases (48.48%) showed ischemic penumbra with diffusion perfusion mismatch with three cases presenting within the first 4 h managed by intravenous thrombolytic therapy and 13 cases presenting later than 4 h, 10 of whom were managed by endovascular intervention. The group with ischemic penumbra showed significant positive correlation with favorable clinical outcome while the group without ischemic penumbra showed significant positive correlation with poor clinical outcome. Quantitative ASL values were statistically significantly higher (p ≤ 0.05) in patients with favorable clinical outcome than those with poor clinical outcome. The estimated cut off values of ASL absolute cerebral blood flow and relative cerebral blood flow to predict favorable or poor outcome using ROC curve analysis were 19 ml/100gm/min and 74% compared to the contralateral side respectively. Conclusion The use of MRI as a primary diagnostic tool in arterial ischemic stroke with the application of non-contrast ASL perfusion sequence allows precise detection of perfusion deficit and diffusion perfusion mismatch (penumbra) and provides a reliable insight into outcome prediction.